Which of the following equations is equivalent to the equation 6x – y = 1? A. y = 6x – 1 B. y = 6x + 1 C. y = -6x + 1

Question

Which of the following equations is equivalent to the equation 6x – y = 1?
A. y = 6x – 1
B. y = 6x + 1
C. y = -6x + 1
D. y = -6x – 1

in progress 0
Ruby 2 weeks 2021-09-13T12:25:34+00:00 2 Answers 0

Answers ( )

    0
    2021-09-13T12:26:51+00:00

    Answer:

    A

    Step-by-step explanation:

    6x – y = 1

    try to make ”y” only right side.

    (add y on both sides)

    6x – y + y = 1 + y

    6x = 1 + y

    (add -1 on both sides)

    6x -1 = 1 + y -1

    6x -1 = y

    Hope this helps ^-^

    0
    2021-09-13T12:27:10+00:00

    Answer:

    A. y = 6x – 1

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )